The twisted relation between Pnu and SWEET transporters. Issue 4 (April 2015) - Jaehme, Michael; Guskov, Albert; Slotboom, Dirk Jan
Highlights SWEET and Pnu transporters have similar structures but lack sequence similarity. A topological difference also raises questions about their evolutionary relatedness. A 3D domain swap can explain the topological differences. We propose a pathway by which the SWEET and Pnu transporters may have diverged.